Effectiveness of Using eLDirU-Based Blended Learning Model to Prevent Post-Pandemic Learning Loss in Basic Swimming Practicum - Bayu Suko Wahono (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The Covid-19 pandemic that has occurred in the past two years has changed many sectors, including the education sector. Learning activities that are usually carried out face-to-face have to be carried out online. This of course can trigger learning loss in students. Especially in basic swimming lessons which require practice to ensure students understand and can practice various styles in swimming. Blended learning in this study is a model that combines eLDirU-based online learning and offline learning, which is deemed appropriate to prevent learning loss in students. This research is a pre-experimental with one group pre-test and post-test design. The population in this study were 40 second semester students majoring in Physical Education for the 2021/2022 academic year. The sampling technique used total sampling with a sample of 40 students. The data used in the form of student practice results in basic swimming practicum learning, then analyzed using univariate and bivariate analysis. The results of this study indicate that there is an effect using the eLDirU-based blended learning model to prevent learning loss after the Covid-19 pandemic in basic swimming practicum with an Asymp. Sig (2-tailed) 0,000. It is hoped that learning using a blended learning model based on eLDirU can prevent learning loss for students, not only in basic swimming practicum, but also in other subjects.